From Teleology to Backward Causation: How Do They Contribute to Our Understanding of the Nature of Concepts? - Poręba, Marcin (Eidos. A Journal for Philosophy of Culture, 2024)
The paper analyses the traditional concept of teleology, as well as its modern descendant, the concept of function (as used in the context of so-called functional explanations), against the background of such notions as purposive action, concepts, causality, time, and space-time. The author distinguishes several meanings of teleology and shows that their dialectics reveal their dependence on the concept of backward causation. The classical approach to backward causation, due famously to Michael Dummett, according to which it is a relation between items such as macroscopic things, events, actions, and so on, is rejected in favor of the view that future causes should be conceptualized in probabilistic terms. The paper lays special stress on the issue of concepts and their proper treatment as nonlocal entities, as opposed to their understanding as wholly present at dimensionless points in space-time. Using this approach, the author argues for the following disjunction: When trying to account for teleology and purposive action, we must either deeply reconsider the traditional, local view of concepts, or we must take backward causation seriously. It is of the nature of disjunction that both alternatives may eventually turn out to be true.